The Unpaid Piper Calls the Tune: Popular Education in the Face of Bureaucracy - Tom Heaney (Adult Education Research Conference, 2000)
Reflecting on possibilities for realizing social change through popular education, this study examines the promise and reality of Paulo Freire’s legacy in the context of an urban literacy center for Latino immigrants.